Reduced Hippocampal Subfield Volume in Schizophrenia and Clinical High-Risk State for Psychosis - Sasabayashi, Daiki; Yoshimura, Ryo; Takahashi, Tsutomu; Takayanagi, Yoichiro; Nishiyama, Shimako; Higuchi, Yuko; Mizukami, Yuko; Furuichi, Atsushi; Kido, Mikio; Nakamura, Mihoko; Noguchi, Kyo; Suzuki, Michio (Frontiers in Psychiatry, 2021)
Magnetic resonance imaging (MRI) studies in schizophrenia demonstrated volume reduction in hippocampal subfields divided on the basis of specific cytoarchitecture and function. However, it remains unclear whether this abnormality exists prior to the onset of psychosis and differs across illness stages. MRI (3 T) scans were obtained from 77 patients with schizophrenia, including 24 first-episode and 40 chronic patients, 51 individuals with an at-risk mental state (ARMS) (of whom 5 subsequently developed psychosis within the follow-up period), and 87 healthy controls. Using FreeSurfer software, hippocampal subfield volumes were measured and compared across the groups. Both schizophrenia and ARMS groups exhibited significantly smaller volumes for the bilateral Cornu Ammonis 1 area, left hippocampal tail, and right molecular layer of the hippocampus than the healthy control group. Within the schizophrenia group, chronic patients exhibited a significantly smaller volume for the left hippocampal tail than first-episode patients. The left hippocampal tail volume was positively correlated with onset age, and negatively correlated with illness duration and duration of medication in the schizophrenia group. Reduced hippocampal subfield volumes observed in both schizophrenia and ARMS groups may represent a common biotype associated with psychosis vulnerability. Volumetric changes of the left hippocampal tail may also suggest ongoing atrophy after the onset of schizophrenia.